Potential Risk of Work Accident in The Production Process of Gudeg Chicken using The Failure Mode and Effect Analysis (FMEA) Method - Tasyarafa Shelia Khairani; Rosa Amalia (Agroindustrial Journal, 2022)
Every agricultural industry has a potential risk of work accidents, one of which is at the Micro, Small and Medium Enterprises (MSMEs) level in Yogyakarta. Gudeg producers as one of the MSMEs in the traditional culinary also have various types of work accident risks in their production process, including in the process of producing Gudeg Chicken. Overall, the process of producing Gudeg Chicken includes sorting, washing, cooking, and distribution. The results of the initial observations indicated that workers in sorting division had the complaints of back pain and several work accidents have occurred in the production division of Gudeg Chicken. Hence, it is deemed necessary to analyze the risk of work accidents occurred. The analysis of work accident risks was done using the Failure Mode and Effect Analysis (FMEA) method by considering severity, occurrence, and detection values to obtain a Risk Priority Number (RPN). The results were then analyzed using a Pareto diagram to determine the work accident with the highest risk. Recommendations for improvement were given using the Hazard Identification Risk Assessment and Risk Control (HIRARC). The results showed that the highest risk of work accidents was related to the position of sitting that is not ergonomic in the process of sorting Gudeg Chicken. The elimination of these risks does not need to be carried out, but it needs to do substitution of production areas, engineering controls with modifications towards the tables or chairs of employees, administrative controls, and the use of Personal Protective Equipment.